1951
DOI: 10.1042/bj0490165
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies of toxic agents. 3. The isolation of 1- and 2-naphthylsulphuric acid and 1- and 2-naphthylglucuronide from the urine of rats dosed with 1- and 2-naphthol

Abstract: The determination ofthe so-called 'ethereal sulphate content' of urine is a simple analytical procedure, and there are many reports in the literature which show that the administration of phenols to experimental animals is followed by an increased excretion ofethereal sulphates in the urine. On the other hand,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1961
1961
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…1-NT has been reported to be metabolized only by glu curonidation and sulfation [28], In agree ment with this, no other metabolites were found in the present study. The possibility was investigated that the lung might possess high levels of (3-glucuronidase and/or sulfa tase which could hydrolyze the correspond ing conjugates.…”
Section: Discussionsupporting
confidence: 82%
“…1-NT has been reported to be metabolized only by glu curonidation and sulfation [28], In agree ment with this, no other metabolites were found in the present study. The possibility was investigated that the lung might possess high levels of (3-glucuronidase and/or sulfa tase which could hydrolyze the correspond ing conjugates.…”
Section: Discussionsupporting
confidence: 82%
“…There is an increase in glucuronide formation when the naphthol concentration in the perfusion medium is increased from 0.2 to 0.5 mM, but higher concentrations do not significantly increase this rate. There are only two major routes of naphthol metabolism: glucuronidation and sulfate ester formation [13]. Thus, a balance sheet of the metabolites can be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The product had the R. of 1-naphthol, suggesting that the original radioactivity was probably present as 1:2-dihydro-1:2-dihydroxynaphthalene (Young, 1947). In agreement with Berenbom & Young (1951) and Boyland & Wiltshire (1953), the diol could not be detected in the urine of rats treated with l-naphthol.…”
Section: Resultsmentioning
confidence: 75%
“…Berenbom & Young (1951) and Boyland & Wiltshire (1953) have concluded that rats and rabbits receiving 1-naphthol produce 1-naphthol, 1-naphthyl sulphate and 1-naphthyl glucosiduronic acid. Two of the additional metabolites which we have found in rats, 1:2-dihydro-2-hydroxy-1naphthyl glucosiduronic acid and 1-naphthylmercapturic acid, may be the result of conjugations involving 1:2-dihydro-1:2-dihydroxynaphthalene, which has not been identified as a product of 1-naphthol metabolism in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation